Architectural Identity: Lithuanian Exiles’ Debate on National Style in 1950s and 1960s North America - Petrulis, Vaidas (Landscape Architecture and Art, 2024)
The article examines the architectural endeavours of the Lithuanian diaspora in North America, with a particular focus on the ways in which World War II refugees leveraged architecture to strengthen Lithuanian identity and communicate the Soviet occupation to the international community. It delves into the use of architecture as a political tool by the exile community, highlighting how national dignity served as a key architectural motivation. The research leads to the assumption that despite the tension between national romanticism and the prevailing mid-century modernism, Lithuanians managed to link national sentiment with a broader critique of modernism, which was evident in the 1950s and 1960s. Additionally, the article outlines the primary architectural strategies employed to demonstrate a distinct Lithuanian character. Through this analysis, the article sheds light on the intellectual framework that facilitated the creation of unique architectural monuments emblematic of the Lithuanian spirit in North America.